Relationship between alcoholism addiction and periodontitis. An in vivo study using drinking-in-darkness protocol in rats. - García-Hernández, Ana L. (Journal of Oral Research, 2020)
Periodontal disease (PD) has been considered a probable risk factor for several systemic diseases. Among them, PD is presumed to be one of the possible etiologies of chronic illness of the central nervous system. In this context, poor oral health and PD is associated with substance abuse in humans. However, if periodontal lesions can produce addiction is unknown. This paper aims to evaluate the possibility that chronic periodontal injury (CPL) can cause ethanol binge intake in drink-in-darkness (DID) protocol in rats. In CPL group (n=10) experimental damage was done to the periodontal tissue of the second maxillary molar, the control group (n=9) received sham injury. Forty-three days after CPL the intake of ethanol was assessed using several concentrations in DID experiment. During the DID experiment, we observed significant differences between the binge-type consumption of ethanol at the lowest concentration of 10% (p=0.01). Differences in consumption of 20% ethanol are observed during a few days (p=0.04), and there are no differences in consumption at 40% concentration of ethanol (p=0.2). It is concluded that chronic periodontal lesion leads to alcoholism in Wistar rats.